Videoscribe as a Media to Improving Arabic Listening Skills to Students - Juliarni, Juliarni; Hasmawati, Hasmawati; Syaputra, Arlian Fachrul (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstract. This research is a classroom action research (CAR) which aims to explain the planning, teacher and student activities, and improving students' Arabic listening skills by using videoscribe  learning media.The subjects of this study are 24 students in class VIID MTs DDI Cambalagi Maros. The data collection techniques in this study are observation and test. This research was carried out in two cycles and each cycle consisted of two meetings. The results of the study showed that there was an increase in students' listening ability by 10% from cycle I to cycle II. These results show that videoscribe  learning media can be applied in improving students' Arabic listening skills Keywords: Listening, Arabic, videoscribe media